Assessing the Damage of Personal Data Breach: A Case Study of Bangkok Metropolitan Area - Junpakdee, Abhisit (Economics and Business Administration Journal Thaksin University, 2022)
The objectives of this study are (1) assess the damage of personal data breach by using Contingent Valuation Method and Censored Regression Model to estimate willingness to pay for privacy and security of personal data. (2) investigate the determinants of willingness to pay for privacy and security of personal data of the 549 samples who live in Bangkok Metropolitan region. The result revealed that the willingness to pay for privacy and security of personal data is 2,390.66 baht per person per year. The economic value of damage of personal data breach from e-Commerce platforms occurred in November 2020 in Thailand estimated from this study was up to 31,078.56 million baht. The initial bid price, age, marital status, income, communication cost, knowledge and understanding of personal data, experience of personal data breach, the importance of personal data privacy, and risk perception of sharing personal data were correlated to the willingness to pay with a statistically significant.